PREDIKSI PERMEABILITAS MENGGUNAKAN METODE LOG DAN PORE GEOMETRY STRUCTURE (PGS) PADA DAERAH CEKUNGAN JAWA BARAT UTARA - Ayu Yuliani; Ordas Dewanto; Karyanto Karyanto; Ade Yogi (Engineering Faculty Universitas Lampung, 2020)
Determination of reservoir rock properties is very important to be able to understand the reservoir better. One of these rock properties is permeability. Permeability is the ability of a rock to pass fluid. In this study, the calculation of permeability was carried out using log and PGS (Pore Geometry Structure) methods based on core data, logs, and CT scans. In the log method, the calculation of permeability is done by petrophysical analysis which aims to evaluate the target zone formation in the form of calculation of the distribution of shale content (effective volume), effective porosity, water saturation, and permeability. Next, the determination of porosity values from CT Scan. Performed on 2 data cores of 20 tubes, each tube was plotted as many as 15 points. The output of this stage is the CT Porosity value that will be used for the distribution of predictions of PGS permeability values. In the PGS method, rock typing is based on geological descriptions, then calculation of permeability predictions. Using these two methods, permeability can be calculated in the study area. The results of log and PGS permeability calculations that show good correlation are the results of calculation of PGS permeability. It can be seen from the data from the calculation of PGS permeability approaching a gradient of one value with R2 of 0.906, it will increasingly approach the core rock permeability value. Whereas the log permeability calculation for core rock permeability is 0.845.